(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to analyze the influence of leadership and work overload on turnover intention, with burnout as a mediating variable in employees of PT Sari Buana. The problem of high turnover intention is the main challenge for the company, which is suspected to be influenced by ineffective leadership style and excessive workload. This condition is exacerbated by burnout experienced by employees, characterized by physical and emotional fatigue, and decreased work enthusiasm. This study uses a quantitative approach involving 270 respondents, employees of PT Sari Buana. Data collection techniques were carried out through questionnaires, with data analysis using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The results of the study showed that leadership had a significant effect on burnout. Then burnout had an effect on turnover intention. In addition, burnout was also proven to mediate the relationship between leadership and turnover intention. These findings provide important implications for company management in formulating more effective human resource management strategies, especially in forming supportive leadership and creating a work environment that can reduce the risk of burnout.